Solidarność Podbeskidzia . pismo NSZZ "Solidarność" Region Podbeskidzie, no. 118, 1989 - [ed. Andrzej Kabat et al.] (NSZZ "Solidarność" Region Podbeskidzie, 1989)
Creation and circulation: After introduction of the Martial Law republished underground in March 1982 without continuous numeration with 1980-1981 edition. Republished again in May 1991, first issue numbered 153(1991) which is the total sum of issues published before and after Martial Law. Published until December 1995. Since 1996 "Solidarność Podbeskidzia"